The potential of craft industries based on Javanese ethnic culture and the local economy in Indonesia: perspectives of creativity - Avianto, Bhakti Nur; Ulumuddin, Ihya; Marjanto, Damardjati Kun; Sudrajat, Unggul; Atmadiredja, Genardi (Creativity Studies, 2024)
This paper aims to determine the extent to which the potential for developing craft industries based on Javanese ethnic culture can improve local economic development and help empower the local community. A qualitative method with case study research approach. Meanwhile, to measure the potential for growing craft industries based on Javanese ethnic culture, the SWOT (strengths, weaknesses, opportunities, threats) analysis–analytic hierarchy process is used by collecting primary data through group discussions while secondary data with questionnaires. Developing craft industries based on Javanese ethnic culture can contribute to local economic development by utilizing abundant human resources, adding concrete employment opportunities, facilitating licensing, maximizing the potential an open art market, and anticipating goods cheaper competition from foreign as well as the entry threatened free trade that would replace the existence of craft products based on Javanese ethnic culture. Efforts are carried out by business actors, manufacturing industry, and arts community to helping facilitate various promotional business opportunities. In addition, the government has made a policy direction for local economic development by balancing foreign and local players to deal with technological innovations and the rapidly changing character of the market.